(untitled) (Research, Society and Development, 2023)
The present study aimed to characterize the population of individuals who suffered sexual violence between the years 2015 to 2019, to describe the characteristics of the aggression and the number of occurrences in that same period in the state of Sergipe. This is a quantitatively descriptive ecological study. During the study period, 5,484 cases of interpersonal/self-inflicted violence and 1,228 cases of sexual violence among children, adolescents, adults and the elderly were reported, with the highest number of records being observed in 2019 with 303 cases (25%). Among the variables that were analyzed, the age group of individuals who suffered the most sexual violence was 10 to 14 years old with 323 cases (26%), of the main causes of the act of sexual violence there is a greater number among friends/acquaintances with 319 cases (26%), regarding gender, a higher prevalence was identified with the female gender - about 87%. The epidemiological data collected in this study were obtained by consulting the Ministry of Health database, DATASUS, with data from the Information System for Notifiable Diseases through the International Classification of Diseases.